Risk factors of Acute Respiratory Infection (ARI) in under-fives in a rural hospital of Central India - Amar M. Taksande; Mayuri Yeole (Hygeia Press di Corridori Marinella, 2015)
Introduction: Acute Respiratory Infection (ARI) is a major cause of morbidity and mortality in developing countries in children especially in under-fives. Every year in the world, about 13 million under-5 children dies, 95% from developing countries; one third of total deaths are due to ARI. The aim of this study was to identify the significant risk factors for ARI in children less than five years of age living in rural areas of Central India. Methods: A hospital based case control study was undertaken to determine risk factors associated with respiratory tract infections in children. Children less than 5 years admitted in a pediatric ward with diagnosis of ARI were enrolled in the study as cases (n = 300) while the same number of controls (n = 300) were selected from neighborhood and were matched for age, sex and religion. Details of risk factors in cases and controls were recorded in pre-designed proforma. Results: A significant association was found between ARI and lack of breastfeeding, nutritional status, immunization status, delayed weaning, prelactal feeding, living in overcrowded conditions, mothers' literacy status, low birth weight and prematurity. Among the environmental variables, inadequate ventilation, improper housing condition, exposure to indoor air pollution in form of combustion from fuel used for cooking were found as significant risk factors for ARI in under-fives. Conclusions: ARIs are affected by socio-demographic and socio-cultural risk factors, which can be modified with simple interventions. The various risk factors identified in this study were lack of breastfeeding, undernutrition, delayed weaning, overcrowding and prelactal feeding.